An uncommon variant of an uncommon disease: A Caucasian adolescent with apical hypertrophic cardiomyopathy diagnosed with myocardial perfusion imaging - Rami Zein; Zaid Al-Faham; Jason Mouabbi; Edouard Daher (World Journal of Nuclear Medicine)
Apical hypertrophic cardiomyopathy (ApHCM) is a subtype of HCM. This variant is more common in the Asian population when compared to North American patients. Patients may present with arrhythmias, heart failure, myocardial infarction, chest discomfort, fatigue, and presyncope or syncope. Initial evaluation requires electrocardiogram and two-dimensional echocardiogram. T-wave inversion in the precordial leads as well as hypertrophy of the left ventricle is hallmarks of the disease. Cardiac magnetic resonance (CMR) imaging is the most specific and sensitive imaging modality. In patients with contraindications for CMR, myocardial perfusion imaging (MPI) has been described to have diagnostic characteristics for ApHCM. MPI images demonstrating a “solar polar” map pattern and increased apical tracer uptake in single-photon emission computed tomography horizontally and vertical long-axis slices are consistent with the diagnosis of ApHCM. Herein, we present a case of a Caucasian adolescent female who underwent a cardiac screening to rule out hypertrophic obstructive cardiomyopathy. Initially, the patient was unable to undergo CMR, and an MPI was utilized to assist with the diagnosis of ApHCM.